Totally implantable catheter embolism: two related cases - Ribeiro, Rodrigo Chaves (2008)
ConTExT AnD oBJECTIVE: Long-term totally implantable catheters (e.g. Port-a-Cath®) are frequently used for long-term venous access in children with cancer. The use of this type of catheter is associated with complications such as infection, extrusion, extravasation and thrombosis. Embolism of catheter fragments is a rare complication, but has potential for morbidity. The aim here was to report on two cases in which embolism of fragments of a long-term totally implantable catheter occurred. DESIGn AnD SETTInG: Case series study at Hospital do Servidor Público Estadual, São Paulo. METHoDS: Retrospective review of catheter embolism in oncological pediatric patients with long-term totally implantable catheters. RESULTS: The fi rst patient was a 3-year-old girl diagnosed with stage IV Wilms’ tumor. Treatment was started with the introduction of a totally implantable catheter through the subclavian vein. At the time of removal, it was realized that the catheter had fractured inside the heart. An endovascular procedure was necessary to remove the fragment. The second case was a boy diagnosed with stage II Wilms’ tumor at the age of two years. At the time of removal, it was noticed that the catheter had disconnected from the reservoir and an endovascular procedure was also necessary to remove the embolized catheter. ConCLUSIon: Embolism of fragments of totally implantable catheters is a rare complication that needs to be recognized even in asymptomatic patients.